2008
DOI: 10.1016/j.cell.2008.03.026
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2, a Negative Regulator of Innate and Adaptive Immunity that Maintains Immune Homeostasis

Abstract: Immune homeostasis is essential for the normal functioning of the immune system, and its breakdown leads to fatal inflammatory diseases. We report here the identification of a member of the tumor necrosis factor-alpha-induced protein-8 (TNFAIP8) family, designated TIPE2, that is required for maintaining immune homeostasis. TIPE2 is preferentially expressed in lymphoid tissues, and its deletion in mice leads to multiorgan inflammation, splenomegaly, and premature death. TIPE2-deficient animals are hypersensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
480
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(498 citation statements)
references
References 28 publications
17
480
0
1
Order By: Relevance
“…30 Based on sequence homology, a TNFAIP8 family of proteins has very recently been defined consisting of TNFAIP8, TIPE1 (TNFAIP8Like1), TIPE2 and TIPE3. 31 The TNFAIP8 family members do not share significant sequence homology with other proteins apart from limited homology within the DED. However, a dramatic breakthrough in identifying their role has come with the generation of Tipe2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Based on sequence homology, a TNFAIP8 family of proteins has very recently been defined consisting of TNFAIP8, TIPE1 (TNFAIP8Like1), TIPE2 and TIPE3. 31 The TNFAIP8 family members do not share significant sequence homology with other proteins apart from limited homology within the DED. However, a dramatic breakthrough in identifying their role has come with the generation of Tipe2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, a dramatic breakthrough in identifying their role has come with the generation of Tipe2 À/À mice. 31 The Tipe2 À/À mice exhibit inflammation in many organs, splenomegaly and premature death with defective innate and adaptive immune processes. TNFAIP8 may be the molecular link between glucocorticoidmediated cell death and immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-α-inducible protein 8 (TNFAIP8 or TIPE) family are very recently identified proteins and induced by TNF-α stimulation and by activation of transcription factor NF-κB (Patel et al, 1997;Kumar et al, 2000). TNFAIP8 family consists of TNFAIP8, TIPE1 (TNFAIP8L1), TIPE2 (TNFAIP8L2) and TIPE3 (TNFAIP8L3), which share considerable sequence homology to regulate cell functions (Freundt et al, 2008;Sun et al, 2008). The early studies had showed that TNFAIP8 is an oncogenic factor that may play a role in tumor progression, and exogenous expression of TNFAIP8 enhances cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, silencing of TIPE2 expression may counteract the reduced inflammation and myocardial injury in NOD2-/-ischemic mice (27). Furthermore, down-regulation of TIPE2 expression may increase the expression of pro-inflammatory factors including IL-1, IL-10, IL-12 and tumor necrosis factor-α, which in turn induce liver inflammation and the progression of liver disease in TIPE2 -/-mice (16). In the present study, it was demonstrated that the expression of TIPE2 was reduced in the PBMCs of patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2) is a gene that was initially identified in a mouse model of autoimmune encephalomyelitis (16). As a type of tumor necrosis factor-α-induced protein-8, TIPE2 is primarily expressed by the myeloid and lymphoid immune cells, particularly by T lymphocytes, mononuclear cells and macrophages (17,18).…”
Section: Introductionmentioning
confidence: 99%